2011
DOI: 10.1038/ijo.2011.184
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of inhibitory control in response to food-associated cues and attentional bias of obese participants and normal-weight controls

Abstract: OBJECTIVE: Starting from a model of impaired response inhibition and salience attribution for addictive behaviour we investigated whether obese participants show a greater impairment of inhibitory control in response to food-associated cues compared with neutral stimuli and whether this is seen in normal-weight control subjects. In addition, we questioned whether an attentional bias towards food-associated cues can be observed in an early stage of information processing. DESIGN: Control-group study including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
120
4
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(142 citation statements)
references
References 33 publications
9
120
4
3
Order By: Relevance
“…(51,52) ). Moreover, one study explicitly tested that healthy and obese individuals alike paid significantly more attention to food pictures than to non-food pictures, independent of their hunger or satiety state ( (19) , see data on eye-tracking).…”
Section: Attention Bias For Food and Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…(51,52) ). Moreover, one study explicitly tested that healthy and obese individuals alike paid significantly more attention to food pictures than to non-food pictures, independent of their hunger or satiety state ( (19) , see data on eye-tracking).…”
Section: Attention Bias For Food and Obesitymentioning
confidence: 99%
“…by testing correlations) if craving and/or hunger is associated with attention biases for food. Of the thirty reviewed studies, eleven measured craving (46,48,50,51,59,61,62,68,(72)(73)(74) and seventeen assessed hunger (19,44,(47)(48)(49)(50)(51)54,58,(60)(61)(62)(63)65,68,69,72) (with an overlap in seven studies assessing both). Eleven of these studies tested the relation of attention bias and craving or hunger statistically.…”
Section: Attention Bias For Food and Cravingmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have previously been used to examine attention to food-related stimuli in normal weight populations in both a fasted and satiated condition (20)(21)(22) . More recently research has begun to focus on visual attention to food-related stimuli in individuals who are overweight or obese (15,(23)(24)(25)(26)(27)(28)(29) . Results from these studies however have been inconsistent and this may be due in part to the methodology used to measure attention.…”
Section: Incentive Sensitisation: Weight Status: Eye Tracking: Visualmentioning
confidence: 99%
“…In comparison, Nijs et al (27) using a between-subject design, recorded self-reported hunger levels using a visual analogue scale in participants following a 17 h fast and in participants provided with a liquid-based study meal. Loeber et al (25) also assessed self-reported hunger levels using a visual analogue scale and participants were instructed to refrain from eating at least 3 h before the testing session.…”
Section: Effects Of Satiationmentioning
confidence: 99%